Use of Residues From the Cellulose Industry and Sugarcane Bagasse in Particleboards - da Silva, Sérgio A. M. [UNESP]; Minillo, Larissa Q. [UNESP]; Aquino, Vinícius B. De M.; Lahr, Francisco A. R.; Christoforo, André L. (FapUNIFESP (SciELO), 2021)
The use of alternative materials such as lignocellulosic residues in the production of particleboards has increased considering that these residues are produced in large volumes and often do not have an appropriate destination. This research studied the use of residues from cellulose industries, sugarcane bagasse, and castor oil-based polyurethane resin in the production of wooden panels and evaluated the influence of using these residues on the physical and mechanical properties of the panels. The products were manufactured according to the Brazilian standard ABNT NBR 14810 and the requirements of the panels were evaluated based on national and international standards. All treatments partially met the regulatory requirements. The addition of bagasse led to an improvement in physical and mechanical properties, with treatment 2 (50% wood residue and 50% bagasse) presenting the best performance, which indicates the possibility of using panels with residues with non-structural purpose in environments to improve the thermoacoustic performance of rural buildings. The statistical analysis indicated that the percentage of bagasse was significant, improving the evaluated properties.
Keywords: castor oil-based resin; Eucalyptus; Industrial residues; particleboards; sugarcane bagasse